HEXIM1 is a critical determinant of the response to tamoxifen - Ketchart, Wannarasmi (2011)
Tamoxifen resistance is a major problem in the treatment of Estrogen Receptor (ER) positive patients. We have previously reported that Hexamethylene bis-acetamide Inducible Protein 1 (HEXIM1) inhibits ERα activity by competing with ERα for binding to cyclin T1, a subunit of Positive Transcription Elongation b (P-TEFb). This results in the inhibition of the phosphorylation of RNA polymerase II (RNAPII) at serine 2 and the inhibition of transcription elongation of ERα target genes. Since HEXIM1 can inhibit ER activity, we examined whether it plays a critical role in the inhibitory effects of tamoxifen on ER. We observed that tamoxifen induced HEXIM1 recruitment to the promoter region of ER target genes and decreased the recruitment of cyclin T1 and serine 2 phosphorylated RNAPII to the coding regions of these genes. Conversely, in cells wherein HEXIM1 expression has been downregulated we observed attenuation of the inhibitory effects of tamoxifen on estrogen-induced cyclin T1 recruitment to coding regions of ER target genes. As a consequence, downregulation of HEXIM1 resulted in the attenuation of the repressive effects of tamoxifen on estrogen-induced gene expression and proliferation. Conferring clinical relevance to our studies is our analysis of human breast cancer tissue samples that indicated association of lower expression of HEXIM1 with tumor recurrence in patients who received tamoxifen. Our studies provide a better understanding of the mechanistic basis for the inhibitory effect of tamoxifen on ER activity and may suggest new therapeutic targets for the treatment of tamoxifen resistant breast cancer.